The Rh problem: a personalized history - Diamond, Louis K. (The Turkish Journal of Pediatrics, 1982)
-
Keywords: anti-Rh gamma globulin; erythroblastosis fetalis; exchange transfusion; hyperbilirubinemia; kernicterus; newborn; Rh isoimmunization